Is variety of species-rich semi-natural Mesobromion grasslands detectable with functional approach? - Kaligarič, Mitja (Annales. Series historia naturalis, 2005)
The aim of the study was to compare how the relevés of species-rich dry grasslands (classis Festuco-Brometea) in Central and Eastern Slovenia differ among each other on the basis of floristic composition and of 11 Plant Functional Traits (PFTs). On the basis of floristic structure and cover values, the relevés were classified in three well separated clusters. In the PCA ordination, the first axes suggested a gradient of soil pH, while the second, floristically based gradient, was interpreted as soil humidity. On the basis of selected traits, 3 PFTs were clustered, but not clearly interpreted. Despite differences in environmental parameters across Slovenia (climate, geographical position, altitude, soil conditions) and variety of land use disturbances - drivers of floristic variety, no discernible difference in vegetation structure in terms of selected plant traits were perceived by PCA ordination. It could be concluded that secondary dry grasslands share rather uniform functional types with not clearly detectable structural differences among them.
Keywords: analiza; biogeografija; biogeography; botanika; Mesobromion; Rhododendron-Park Bremen; Slovenia; Slovenija; travišča; travniki; vegetacija